2019
DOI: 10.1039/c9ra00005d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction behaviors and structural characteristics of zein/NaTC nanoparticles

Abstract: Bile salts are biosurfactants distributed in the human gastrointestinal tract, which can significantly influence the structure and functions of orally administrated components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…On the other hand, Bosaeus et al [88] investigated soy bean proteins as alternatives to meat proteins and did not find significant influences on ileostomy bile acid concentrations. A recent study of Wang and Fan [89] focused on structural characteristics of the interaction between zein, a plant protein isolated from maize, and sodium taurocholate. The study showed sodium taurocholate-dependent changes in secondary and tertiary protein structures and electrostatic binding between the bile salt and the protein.…”
Section: Interactions Between Bile Acids and Proteinsmentioning
confidence: 99%
“…On the other hand, Bosaeus et al [88] investigated soy bean proteins as alternatives to meat proteins and did not find significant influences on ileostomy bile acid concentrations. A recent study of Wang and Fan [89] focused on structural characteristics of the interaction between zein, a plant protein isolated from maize, and sodium taurocholate. The study showed sodium taurocholate-dependent changes in secondary and tertiary protein structures and electrostatic binding between the bile salt and the protein.…”
Section: Interactions Between Bile Acids and Proteinsmentioning
confidence: 99%
“…The use of UV-Vis absorption, fluorescence and circular dichroism have shed light on the interactions between zein and NaTC at submicellar BS concentration. The combination of techniques showed that protein undergoes conformational changes in the secondary and tertiary structure in the mixed protein-BS aggregate above certain NaTC concentration [69]. The experimental procedure was carried out at pH 4, at which electrostatic binding is likely to occur between positively charged zein nanoparticles (NPs) (IP at pH 6.2) and negatively charged NaTC.…”
Section: Bs and Proteinsmentioning
confidence: 99%
“…This study investigated the interaction between bile salts and hydrophilic pharmaceutical grade polymers with the aim to contribute new insights into the impacts of bile salt-polymer interaction on drug solubilisation. Such knowledge would benefit the further exploitation of solid dispersions in the delivery of poorly water-soluble drugs 4 Bile salts are produced by the oxidation of cholesterol in the liver, stored in the gallbladder and excreted into the intestinal lumen, [18] and have been shown to interact with different kind of drug delivery systems, such as β-Cyclodextrins, [19,20] zein protein [21] and gold nanoparticles. [22] They have a rigid tetracyclic steroid ring structure with the convex side of the ring being hydrophobic and the concave side of the ring being hydrophilic.…”
Section: Introductionmentioning
confidence: 99%